The digital economy - Jordan, Tim, 1959- (Cambridge : Polity, 2019)
"Tim Jordan deftly explores the workings of the trillion-dollar digital economy. He discusses the hype and significance surrounding its activities and practices in order to outline important concepts, theory, and policy questions. Rich with case studies, the book is an important reference for those getting to grips with this contemporary phenomenon"--
Introduction: The meaning of the digital economy -- Search -- Social media -- Taxis, hotels and blockchains -- Free online economies -- Online games -- Profit, labour, production and consumption -- Defining the digital economy -- Policy.
Includes bibliographical references and index.
Keywords: Business enterprises -- Technological innovations; Electronic commerce; Information technology -- Economic aspects